Cyclin C influences the timing of mitosis in fission yeast - Banyai, Gabor (Mol Biol Cell, 2017)
The multiprotein Mediator complex is required for the regulated transcription of nearly all RNA polymerase II–dependent genes. Mediator contains the Cdk8 regulatory subcomplex, which directs periodic transcription and influences cell cycle progression in fission yeast. Here we investigate the role of CycC, the cognate cyclin partner of Cdk8, in cell cycle control. Previous reports suggested that CycC interacts with other cellular Cdks, but a fusion of CycC to Cdk8 reported here did not cause any obvious cell cycle phenotypes. We find that Cdk8 and CycC interactions are stabilized within the Mediator complex and the activity of Cdk8-CycC is regulated by other Mediator components. Analysis of a mutant yeast strain reveals that CycC, together with Cdk8, primarily affects M-phase progression but mutations that release Cdk8 from CycC control also affect timing of entry into S phase.